Effects of physical activity, social capital on positive emotions in older adults—A study based on data from the 2022 CFPS survey - Niu, Long; Zhang, Xiaodong; Ma, Yichen (Frontiers in Psychology, 2025)
BackgroundExisting literature indicates that physical activity has a significant positive impact on the positive emotions in older adults; however, the mechanism of the relationship between physical activity and positive emotions remains unclear. This study aims to explore the role of social capital in the relationship between physical activity and positive emotions among older adults.MethodsFirst, the positive mood indicators of the elderly were constructed through the Euclidean distance method, and descriptive statistics and correlation analyses were performed on the relevant variables involved in this paper. Secondly, structural equation (SEM) was used to establish a parallel mediation model to analyze the mediating effect of social capital between physical activity and positive emotions of the elderly. Meanwhile, in order to test the potential influence of gender on the mediating path, this study used Multi-group SEM to divide the samples into two groups of males and females, and compared the path coefficients between groups through the Likelihood Ratio Test (LRT). Finally, the average treatment effect of ATT, i.e., the experimental group, was obtained through the propensity score matching test.ResultThe results show that: (1) Physical activity has a significant positive effect on the positive emotions of older adults. (2) Social capital (i.e., individual social capital and collective social capital) significantly positively influences the positive emotions of older adults. (3) Physical activity has a significant positive effect only on collective social capital, and the mediation analysis reveals that collective social capital plays a significant mediating role in the relationship between physical activity and positive emotions in older adults.ConclusionThis study reveals that physical activity not only directly enhances the positive emotions of older adults, but also exerts an indirect effect by strengthening collective social capital. Therefore, it is recommended that the Chinese government promote the social connections and collective interactions of older adults by providing public spaces, organizing community activities, and strengthening social interaction platforms. These efforts could help improve the positive emotions of older adults and contribute to the achievement of healthy aging goals.